2001
DOI: 10.1128/jvi.75.6.2509-2515.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage K1-5 Encodes Two Different Tail Fiber Proteins, Allowing It To Infect and Replicate on both K1 and K5 Strains of Escherichia coli

Abstract: A virulent double-stranded DNA bacteriophage, ⌽K1-5, has been isolated and found to be capable of infecting Escherichia coli strains that possess either the K1 or the K5 polysaccharide capsule. Electron micrographs show that the virion consists of a small icosohedral head with short tail spikes, similar to members of the Podoviridae family. DNA sequence analysis of the region encoding the tail fiber protein showed two open reading frames encoding previously characterized hydrolytic phage tail fiber proteins. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(124 citation statements)
references
References 38 publications
5
118
0
1
Order By: Relevance
“…Therefore, K5A may more accurately be named K5-95. Dual-specificity has obvious implications for phage evolution and expansion of host range as has been discussed previously (3).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, K5A may more accurately be named K5-95. Dual-specificity has obvious implications for phage evolution and expansion of host range as has been discussed previously (3).…”
Section: Discussionmentioning
confidence: 97%
“…Genetic engineering might thus offer the possibility to extend the host range of a single master T4-like phage. In fact, some coliphages use this strategy naturally: phage Mu inverts the orientation of the receptorinteracting gene by a phage-encoded recombinase (Kamp et al, 1978), and Scholl et al (2001) described a coliphage possessing two different tail fibre proteins that showed the combined host range of phages containing one or the other protein. About 30 different O serotypes must be lysed to cover the majority of EPEC and ETEC strains worldwide (Robins-Browne, 1987;Goodridge et al, 2003).…”
Section: Why E Coli?mentioning
confidence: 99%
“…For endoNE of K1E, hetero-oligomeric structures of 208 and 325 kDa were described, composed of endoNE and a not as yet identified 38-kDa protein (8,18). So far, genes encoding endosialidases have been cloned from four different phages: K1F (11), K1E (18,19), 63D (GenBank accession number AB015437), and the dual specificity phage K1-5 that can infect E. coli K1 and K5 (20). However, recombinant expression of active enzyme has been reported only in the case of endoNE (18,19).…”
mentioning
confidence: 99%